Perception Study on Ergonomics Practices at Malaysian Quarry and Mining Industry - Norhidayah, M. S.; Ahmad Rasdan, Ismail; Norhidayah, Abdullah (Excellent Publishers, 2015)
Ergonomics can be viewed as an approach to decrease injury and illness rates and to improve the overall working conditions for employees by addressing risk factor exposure that may occur during manual task. The goals of this research are to analyze ergonomics risk factor by associating the perception of employer and employees towards their workplace condition in quarry and mining industry. A Questionnaire on Ergonomics Risk Assessment was used to determine the comparison level awareness and perception analysis among quarry and mining industry in Malaysia. The findings of this research prove that the exposure of ergonomics risk factors towards the workers is commonly in moderate level 3.59 in mean for the overall respondent review about the ergonomics risk among the workers at their workplace. Besides that, the most concern in ergonomics is about the awkward posture had 8.8% of them agreed and 6.6% of them totally agreed that they were in awkward posture while doing their work. As s conclusion, assessment of ergonomics in quarry and mining industries will be a platform to provide a safe and healthy working environment.